Sanctions and Embargoes as a Crisis Response Instrument in the Context of the Ukrainian Crisis - Veronika Orieskova; Jan Havko (Communications - Scientific letters of the University of Zilina, 2015)
The paper analyzes the importance of sanctions and embargoes as a tool used by organizations of international crisis management to resolve large-scale crisis events in a peaceful way. The attention is paid to one of these crisis events, the Ukrainian crisis. On the basis of value selected parameters, which are the change of exchange rates and inflation growth in particular countries, it reviews their impact on both stakeholders, namely the countries of the European Union and the Russian Federation.